EFFECTS OF MANAGEMENT PRACTICES AND TAPPING SYSTEM ON LATEX AND DRY RUBBER YIELDS OF RUBBER TREE CLONE RRIT 251 - B. Wiangsamut; M. Koolpluksee; C. Makornpas; C. Chaichuay; R. Chaichuay; M.E.L. Wiangsamut (Journal of Animal and Plant Sciences, 2024)
The cultivation of Hevea brasiliensis, as the main source of natural rubber, is facing the tapping labor shortage and low dry rubber yield problems. Management practices and tapping system could nevertheless remedy these constraints. Accordingly, the study aimed to assess the latex and dry rubber yields of rubber trees clone RRIT 251 under different irrigation with fertilizer management methods and rubber tapping systems. The experiment was laid out in a split-plot design, 4 replications with 3 rubber trees per replication. Two main plot treatments: 1) application of irrigation combined with chemical and organic fertilizers treatment (IF) and; 2)no-irrigation-fertilizer treatment (NIF). Four subplot treatments: 1) (10 cm)S.d/3+ET – tapping 10 cm long of trunk girth (at 45° angle) above an installed bag of ethylene, for 1 day with 2 days interval; 2) (1/2)S.d/2 – tapping half of trunk girth every other day; 3) (1/2)S.2d/3, tapping half of trunk girth for 2 days with 1 day interval (the practice of most para rubber farmers) and; 4) (1/2)S.3d/4, tapping half of trunk girth for 3 days with 1 day interval. The controlled treatment was a combination treatment of NIFx (1/2)S.2d/3. The results showed that both IFx (10 cm)S.d/3+ET and IFx (10 cm)S.d/3+ET combination treatments had significant effects (P≤0.01) in enhancing latex weight per tree, dry rubber weight per tree, latex yield, and dry rubber yield higher than the controlled treatment. IF treatment had a significant effect (P≤0.01) in enhancing latex weight per tree, dry rubber weight per tree, latex yield, and dry rubber yields higher than NIF treatment. Rubber tapping system under (1/2)S.3d/4 had a significant effect (P≤0.01) in enhancing latex weight per tree, dry rubber weight per tree, latex yield, and dry rubber yield while it was significantly (P≤0.01) low under (1/2)S.d/2 as compared with the practice used of most farmers—(1/2)S.2d/3. It is concluded that the application of ethylene under IFx (10 cm)S.d/3+ET management is a better innovation and technology attributable to having 45% less time and less bark area consumed for tapping but with increased dry rubber yield, while IFx (1/2)S.2d/3 spent more time to increase the dry rubber yield, as compared with the controlled treatment.
Keywords: Ethylene; Fertilizer; Irrigation; Latex; Rubber